Effects of 12 weeks of Tai Chi Chuan intervention on the postural stability and self-reported instability in subjects with functional ankle instability: Study protocol for a randomized controlled trial - Ke, Xiao-hua; Huang, Dun-bing; Li, Yin-yan; Li, Xiao-mei; Guo, Jin-hua; Guo, Miao-miao; Yu, Sheng-xian; Ma, Sheng-chao; Jiang, Cai; Lin, Zhong-hua (Frontiers in Neurology, 2022)
Abstract Background: Tai Chi Chuan (TCC) is a physical activity modality that originated in China and is now widely popular all over the world. Although there are a series of articles reporting that TCC can improve balance and other functional symptoms in a variety of populations, including the elderly, stroke patients, and Parkinson's disease patients, its efﬁciency has not been scientiﬁcally and methodically evaluated in subjects with functional ankle instability (FAI). Moreover, there is no literature directly compare TCC and conventional balance training(CBT) interventions for FAI. The objective of this study is to investigate the comparative effects of TCC intervention and conventional balance training protocols in improving postural balance and subjective instability feelings in patients with FAI. Methods: This study will be a single-centre, parallel group, randomized controlled trial. Sixty-eight FAI patients will be included and randomly assigned in a 1:1 ratio to either an intervention group (n =34) or a control group (n=34). The participants in the intervention group will complete twelve weeks of TCC intervention (40min/time, 3 times/week, for 12 weeks) on the basis of health education treatment. The control group will receive health education and 36 conventional balance training sessions during a 12-week period. Outcome measures include postural stability and self-reported feelings of instability at baseline, after the end of the intervention, and 3-month follow-up. The postural stability assessment of FAI patients will be detected by performing static and dynamic postural tests, which will be carried out through a specific balance platform (Techno-body Prokin). Self-reported feelings of instability will be assessed by Cumberland Ankle Instability Tool (CAIT), American-Orthopaedics-Foot-and-Ankle-Society's-Ankle-Hindfoot-Evaluation-Scale (AOFAS-AHES), and the MOS item short from health survey (SF-36). Discussion:This trial will demonstrate whether a 12-week TCC intervention positively affects postural stability and self-reported outcomes in FAI patients. At the same time, the superiority of its clinical efficacy will also be compared with that of conventional balance training. This study may also help to redefine the value of traditional Chinese exercises in the treatment of chronic ankle instability. Trial registration: Chinese Clinical Trial Registry: ChiCTR2100041790. Registration date: 22 March 2021. http://www.chictr.org.cn/edit.aspx?pid=119501&htm=4